Recent developments in nanotechnology transforming the agricultural sector: a transition replete with opportunities. (27th November 2017) - Kim, Dae‐Young; Kadam, Avinash; Shinde, Surendra; Saratale, Rijuta Ganesh; Patra, Jayanta; Ghodake, Gajanan
Abstract: The applications and benefits of nanotechnology in the agricultural sector have attracted considerable attention, particularly in the invention of unique nanopesticides and nanofertilisers. The contemporary developments in nanotechnology are acknowledged and the most significant opportunities awaiting the agriculture sector from the recent scientific and technical literature are addressed. This review discusses the significance of recent trends in nanomaterial‐based sensors available for the sustainable management of agricultural soil, as well as the role of nanotechnology in detection and protection against plant pathogens, and for food quality and safety. Novel nanosensors have been reported for primary applications in improving crop practices, food quality, and packaging methods, thus will change the agricultural sector for potentially better and healthier food products. Nanotechnology is well‐known to play a significant role in the effective management of phytopathogens, nutrient utilisation, controlled release of pesticides, and fertilisers. Research and scientific gaps to be overcome and fundamental questions have been addressed to fuel active development and application of nanotechnology. Together, nanoscience, nanoengineering, and nanotechnology offer a plethora of opportunities, proving a viable alternative in the agriculture and food processing sector, by providing a novel and advanced solutions. © 2017 Society of Chemical Industry